Thermal Effectiveness Analysis of Lube Oil Cooler Fan with Capacity of 40.332 Kg/S with Pressure of 5 Bar - Angga Bahri Pratama; Abdul Razak; Nasya Ayu Lestari Horoni; Sahat Sahat; Nelson Manurung; Berta Br Ginting; Franklin Taruyun Hudeardo Sinaga; Zumhari Zumhari (Newinera Publisher, 2026)
The Lube Oil Cooler Fan is an essential component in the lubrication system of a gas turbine because it maintains lubricating oil temperature within a safe operating range. This study aims to analyze the thermal performance and effectiveness of the Lube Oil Cooler Fan on Gas Turbine GT 1.1 at PT XYZ. The study employed a descriptive quantitative approach using field observation data and heat transfer calculations. The analysis was conducted through the Log Mean Temperature Difference method and heat exchanger effectiveness approach by considering fluid temperature changes, mass flow rates, thermophysical properties, flow characteristics, convective heat transfer coefficients, overall heat transfer coefficient, heat transfer rate, and thermal effectiveness. The results show that the lubricating oil temperature decreased from 61°C to 49°C, while the cooling air temperature increased from 32°C to 53.5°C. The tube side heat transfer coefficient was 40.71 W/m²°C, the shell side heat transfer coefficient was 308 W/m²°C, and the overall heat transfer coefficient was 30.61 W/m²°C. The calculated heat transfer rate was 992.57 W or approximately 0.993 kW. The lubricating oil was identified as the minimum heat capacity fluid, with a heat capacity rate of 33.13 kW/°C. The thermal effectiveness of the Lube Oil Cooler Fan was 41.4%, indicating that the cooler was able to perform its cooling function, although its performance remained moderate. Routine monitoring, stable airflow control, and periodic cleaning are recommended to improve thermal performance.